(untitled) (MEDIEVAL HISTORY OF CENTRAL EURASIA, 2024)
This article analyzes the Kazakh historiography of studying the history of Jochi Ulus. The emphasis is on three different units of scientific output. 1. Candidate and doctoral dissertations. 2. Research projects and reports on them. 3. Individual and collective monographs. Among all Kazakhstan’s dissertations for all the years of independence, only 4 dissertations relate to the history of the ulus of Jochi are highlighted. Among the reports of scientific projects, there are a number of projects that relate to the history of Jochi Ulus. Among the monographs, we can also distinguish a small number of those that are performed at a relatively high scientific level. Scientific articles due to their large number were not considered in this article. The analysis shows that, on the one hand, there is a shortage of scientific research on the history of Jochi Ulus in Kazakhstan. On the other hand, the level of available scientific research on the history of Jochi Ulus is not at a high level.